A diagnostic on-farm survey of the potential of seed drill and transplanter for mechanised rice establishment in Central Laos and Southern Cambodia. (2nd January 2019) - Xangsayasane, Phetmanyseng; Phongchanmisai, Senthong; Vuthea, Chea; Ouk, Makara; Bounphanousay, Chay; Mitchell, Jaquie; Fukai, Shu
ABSTRACT: Due to labour shortages in rural areas, traditional manual transplanting is often no longer feasible and alternative rice establishment methods are required in Central Laos and Southern Cambodia. The work reported here evaluated the potential of a seed drill and transplanter by comparing yield of over 200 crops established by different methods including broadcasting in farmer's fields under their management in 3 seasons in Laos. In Cambodia, yield of rice established by drill planting was compared with farmers' practice by broadcasting in two early wet seasons. When mechanised and manual establishment methods were compared in each of 10 farms in the same season in Laos, drilled crops produced slightly higher yield compared with manual planting. Similarly in Cambodia, the technology package including drill produced slightly higher yield and higher gross margin despite lower plant density than that of the farmer practice based on broadcasting. On the other hand, mean yield established using drill was 26% lower than manually transplanted crops across all seasons and villages in Laos, indicating that possibly drills were used in fields unsuitable to them. Mean yield established using transplanter across all fields was 16% lower than manually transplanted crops. Hill density of crops established from transplanter was lower than that from manual transplanting, and yield increased with increased hill density. The labour requirement and hence establishment cost were greatly reduced compared to manual transplanting. The results show the economic advantage of mechanised rice establishment particularly of seed drills. Abbreviations : WS: wet season; DS: dry season.